2019
DOI: 10.5539/jas.v11n16p159
|View full text |Cite
|
Sign up to set email alerts
|

Substrates and Sowing Depths in the Production of Pansy Seedlings (Viola tricolor L.)

Abstract: The success of seedling production for ornamental or any other crops depends on several factors, including the use of highquality seeds and the choice of suitable substrates. The aim of this work was to evaluate the use of different organic residues as substrates and sowing depths on the emergence and initial development of pansy seedlings. Two lots of pansy seeds were used. Seed lot quality was evaluated for water content determination, 1000-seeds weight, germination, first count of germination, accelerated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The use of biostimulants in the plant early stages can also increase resistance to pests and diseases and the fast establishment of plants, which can increase nutrients absorption and yield (Lana et al 2009;Baldotto & Baldotto, 2014a, 2014b. Reis et al (2019) also observed increased plant improvement with different types of substrates in the production of pansy seedlings (Viola tricolor var. hortensis).…”
Section: Introductionmentioning
confidence: 99%
“…The use of biostimulants in the plant early stages can also increase resistance to pests and diseases and the fast establishment of plants, which can increase nutrients absorption and yield (Lana et al 2009;Baldotto & Baldotto, 2014a, 2014b. Reis et al (2019) also observed increased plant improvement with different types of substrates in the production of pansy seedlings (Viola tricolor var. hortensis).…”
Section: Introductionmentioning
confidence: 99%